Níveis de concentração de elementos terra raras em sedimentos do Rio Pinheiros, São Paulo - Moura, Rodrigo Reis de [UNIFESP] (2014)
This research had as main objective evaluating the concentrations of Rare Earth Elements (REE) in sediments of the Pinheiros River and Billings Reservoir, SP, correlating the determined concentrations of these elements to their origin as natural sources Rocks Local geological context or were a result of anthropogenic inputs. The sediment samples studied were obtained in two sampling campaigns (one in the dry season and another in the rainy) in 05 (five) collection points along the Upper Canal Pinheiros River, between the Traição and Pedreira pumpings plants, and 01 (one) point in the Billings Reservoir, with short testimonies from 25 cm depth. For chemical analysis, the samples were previously dried at 80°C for 48 hours, and subjected to a digestion procedure with HNO3 and HCL concentrated and H2O2. The extracts were diluted and the determinations of the levels of REE were performed on an ICP-AES. The Rare Earth Elements, also identified as lanthanides (La to Lu) plus Sc and Y are elements that have similar chemical behavior. Order to data interpretation, was made a grouping of REE in Light (La, Ce, Pr, Nd, Pm), Medium (Sm, Eu, Gd, Tb) and heavy (Dy, Ho, Er, Tm, Yb, Lu, Sc, Y). These elements are mainly associated with the mineral group of bastnaesita (CO3F), monazite (PO4) and xenotímio (YPO4). The obtained results highlighted a marked characteristic in REE patterns for sedimentary processes is that the uniformity of the abundance patterns observed in several rock types along the study area that may have a major influence on unit schists of the Embu Complex. Comparing the two sampling campaigns in distinct periods (dry and rainy) showed an increase of the concentration values in the rainy season campaign, especially REE-Light. Several references describe the distinct patterns to REE, which indicate the deposition of these elements in arid conditions, whereas under humid conditions there is a slight tendency for not fractionation due to preferential mobility of REE-light in those conditions. The average values of concentration to REE determined ranged from 0,1 a 15,55 mg.kg-1, especially La, Ce, Pr and Nd with a higher concentration than the other elements of the series. Even so, these levels show a very much close levels of crustal rocks and sediments analyzed in comparative studies. We must also mention the anthropogenic inputs, once the ?flúvio-lacustre? environment has raised a record of physical modifications and severe contamination processes physico-chemical according to the urban and industrial development in the area plain of inundation which contributes to potential sources of REE.